PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS ETNOSAINS PADA PEMBELAJARAN IPA SEKOLAH DASAR - DS, Yulistina Nur; Andes Safarandes Asmara; Anggy Giri Prawiyogi; Harmawati; Sinta Maria Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This development research is based on problems in learning IPAS and the low science literacy skills of elementary school students. The purpose of the research is to develop ethnoscience-based digital teaching materials to improve science literacy skills. This research uses R&D with the ADDIE model approach. Data collection techniques include: questionnaires and documentation. The results of research and development show that the material expert validation consists of 3 validators, which obtained an average value of 83 with a very feasible category to use. While the media expert obtained an average value of 86 with a category very feasible to use. Learning experts get an average value of 87 with a category very feasible to use. So it can be concluded that ethnoscience-based digital teaching materials are very feasible to use.